What determines coal consumption for heating residential space in central Asia? - Ranjeeta Mishra; Dina Azhgaliyeva; Zhanna Kapsalyamova; Aiymgul Kerimray; Kamalbek Karymshakov (Asian Development Bank Institute (ADBI), 2021)
Despite complete electrification in Kazakhstan and the Kyrgyz Republic, the reliance on coal for heating residential spaces is high. Using microdata from the national household surveys from Kazakhstan in 2017 and the Kyrgyz Republic in 2016, this study examines the factors affecting residential fuel choice and patterns of consumption for different fuel types-with an emphasis on coal-for heating in the two countries. We employ three models: logit, multinomial logit, and double-hurdle models. The results indicate that access to cleaner and more modern energy infrastructure such as natural gas pipelines and central heating are important for reducing solid fuel consumption, especially in rural areas. Regions with higher coal prices prefer cleaner heating, while regions with higher electricity prices prefer solid fuels. Education is important for the reduction of household solid fuel consumption. The results do not provide evidence that newer houses are more energy efficient.
Keywords: Q41; Q31; Q48; 330; residential heating; coal; Kazakhstan; the Kyrgyz Republic; multinomial logit; double-hurdle model